1983
DOI: 10.3109/10826088309039356
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Effective Components of Alcohol Abuse Prevention Programs: Effects of Fear Appeals, Message Style, and Source Expertise

Abstract: Despite the importance of alcohol abuse prevention programs, the effectiveness of many components of these programs has not been demonstrated empirically. An experiment tested the efficacy of three components of many prevention programs: fear appeals, one- versus two-sided message style, and the expertise of the source. The persuasive impact of this information was examined on 113 ninth-grade students' intentions to abstain from drinking alcohol while they are teenagers. The results reveal that fear appeals ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 14 publications
2
28
0
1
Order By: Relevance
“…These findings add to the accumulating support for the use of strong negative emotional appeals in advertisements aimed at changing health attitudes and behaviours. Such appeals have been shown to be effective in communications regarding seatbelt use,23 smoking cessation,14 24 condom use,25 and alcohol abuse,26 especially when the efficacy of the preventive behaviour was clear. These findings contradict recommendations in the literature that discourage the use of ads featuring short or long term health effects in anti-tobacco media campaigns 1…”
Section: Discussionmentioning
confidence: 99%
“…These findings add to the accumulating support for the use of strong negative emotional appeals in advertisements aimed at changing health attitudes and behaviours. Such appeals have been shown to be effective in communications regarding seatbelt use,23 smoking cessation,14 24 condom use,25 and alcohol abuse,26 especially when the efficacy of the preventive behaviour was clear. These findings contradict recommendations in the literature that discourage the use of ads featuring short or long term health effects in anti-tobacco media campaigns 1…”
Section: Discussionmentioning
confidence: 99%
“…We coded the amount of time between the fear appeal and the measurement of the outcome variable using three discrete categories: (a) The measure occurred the same day as the fear appeal exposure (e.g., Taubman Ben-Ari et al, 2000; Cho & Salmon, 2006; Nabi et al, 2008; Smart & Fejer, 1974; Stainback & Rogers, 1983); (b) the measure occurred one to fourteen days after fear appeal exposure (e.g., Berkowitz, 1998; Kirscht et al, 1978; Muthusamy et al, 2009); and (c) the measure occurred more than fourteen days after fear appeal exposure (e.g., Bagley & Low, 1992; Smith & Stutts, 2003; Witte & Morrison, 1995). We used categories because delayed outcomes often occurred within a specified range – e.g., participants returned to the lab during the following two weeks, but the exact number of days was not specified.…”
Section: Methodsmentioning
confidence: 99%
“…Perceptions of self-efficacy (i.e., perceived ability to perform a rec-ommended response) and response efficacy (i.e., one's beliefs about whether or not a recommended response works to avert a threat) determine whether people are motivated to control the danger (changing one's behavior) or control the fear (changing one's perception of the threat). For example, a study looking at message design for alcohol abuse prevention campaigns indicated that fear appeals are successful in improving adolescents' intentions not to drink (Stainback & Rogers, 1983). Witte and colleagues found, in a study to prevent the spread of genital warts, that fear appeals can be persuasive if the level of fear and the perceptions of response efficacy are high (1998).…”
Section: Introduction Framingmentioning
confidence: 97%